The Effectiveness of Remedial Programs in Islamic Religious Education Learning to Improve Student Achievement in Secondary Schools: A Literature Review - Azka, Zumratul; Nikmah, Mubarakatun; Hidayah, Nurul (FKIP - Universitas Riau, 2025)
Remedial programs in Islamic Religious Education (PAI) learning are needed to help students who have difficulty understanding Islamic concepts, which results in low academic achievement. However, the implementation of this program faces challenges, such as time constraints, lack of resources, and low student motivation. This study aims to analyze the effectiveness of remedial programs on improving student achievement in secondary schools. The method used is qualitative with a literature study approach. Content analysis techniques are used to review various academic sources related to the effectiveness, challenges, and success factors of remedial programs in PAI. The results of the study indicate that remedial programs can improve student understanding, improve learning motivation, and contribute to improving academic achievement. The success of this program is influenced by the role of teachers as facilitators, school and parental support, interactive learning methods, and good time management. However, challenges such as time and resource constraints are still obstacles that need to be overcome with innovative strategies, such as the use of learning technology and peer tutoring approaches. The conclusion of this study confirms that remedial programs play an important role in improving student achievement if implemented with the right strategy. Therefore, it is necessary to develop innovative learning methods, optimize the role of teachers, and continuous evaluation to improve the effectiveness of remedial programs in Islamic Religious Education.